Investigating Employee Engagement: Will Occupational Health Safety Actually Impact Employee Loyalty? - Luki Setiawan Suardi; Renando Meiko Putra; P. Laya Agustin; Anita Maharani (Jurnal Manajemen dan Organisasi, 2022)
The purpose of this study is to examine elements that influence employee loyalty, as viewed through the prism of characteristics that foster the establishment of employee participation, as shown via case studies in financial services organizations. In a number of investigations, it was discovered that occupational health and safety had a significant impact in promoting employee loyalty, and this was confirmed. As a result, the goal of this study is to determine the degree to which employee loyalty is impacted by employee engagement when occupational health and safety is included as a moderator. The notion of employee engagement was the subject of the literature research conducted for this study, followed by employee loyalty and occupational health and safety. Using a quantitative approach, with reference to multivariate analytic methods, with partial least squares, and the decision-making way of looking at the P-values, this research method is carried out. The findings of this study indicate that occupational health safety does not have an effect on the relationship between employee engagement and employee loyalty; however, the presence of occupational health safety will not have an effect on the relationship between employee engagement and employee loyalty.